Employer power and employment in developing countries - Nancy H. Chau; Ravi Kanbur; Vidhya Soundararajan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The issue of employer power is underemphasized in the development literature. The default model is usually one of competitive labour markets. This assumption matters for analysis and policy prescription. There is growing evidence that the competitive labour markets assumption is not valid for employment in developing countries. Our objective in this paper is to review this evidence, to present theoretical and policy perspectives that follow from it, and to highlight areas for further research.
Keywords: J42; O15; 330; employer power; employment; developing countries